Bolsa família: análise da eficiência na segurança alimentar e nutricional na região Norte - Noronha, Thiago Magno Pinheiro (Brasil, 2023)
Food safety is a recurrent topic of discussion in Brazilian society. Public policies on food security have existed since the beginning of the 20th century, and today, consistent policies have been developed that have helped mitigate the problem. In this work, we sought to present the efficiency of the Bolsa Familia program in terms of nutritional food security in the northern region of Brazil. For this, Data Envelopment Analysis (DEA) was used, which measured the efficiency of the Decision Marking Units (DMU) on a set of data separated between inputs (inputs) and outputs (products), in which transfers of Bolsa Família Program resources and products, namely: the Number of adolescents in an inadequate nutritional situation; the Number of children up to 2 years of age in an inadequate nutritional situation; the Number of people living in poverty; the Number of people in extreme poverty; the Infant Mortality Rate (per thousand born) that due to the nature of undesirable products, such variables were inverted by the formula (1/output); due to the nature of undesirable products, such variables were inverted by the formula (1/output). The program was product-oriented in order to maximize its results at a constant level of inputs, with variable returns to scale. It was found that among the 375 municipalities studied, 19 showed efficiency (5%), 4 showed weak inefficiency (1%), 39 showed moderate inefficiency (10%), and 313 showed strong inefficiency (84%). It is concluded that municipalities, as a whole, are inefficient, making it necessary for municipalities to carry out an in-depth analysis of their unique characteristics and the characteristics of the region for the application of public policies that improve the results of the indicators.